The Spreading of Islamic Teachings Through Written Traditions: Reflection of Wawacan Forms in Sundanese Islamic Manuscripts: Penyebaran Ajaran Islam Melalui Tradisi Tulis: Refleksi Bentuk Wawacan dalam Naskah Sunda Islami - Isep Bayu Arisandi (LIPI Press, 2022)
Abstrack This paper aims to reveal the role of the written tradition as a medium for spreading Islamic teachings in Tatar Sunda. There are various teaching themes contained in the texts of manuscript Riwayat Nabi Yusuf (RNY), Pandita Nursaléh (PN), Wawacan Pandita Sawang (PS), Babad Awak Salira (AS), and Pranata Istri ka Carogé (PI), in addition to a commonality that is built on the form of wawacan, as well as the value of the content of Islamic teachings that are so thick. This study reveals the role of the written tradition in recording and conveying Islamic teachings through ancient texts. The five manuscripts that became the object showed that in RNY, PN, PI, and AS the results were copied from other texts. Meanwhile, the theme of Islamic teachings in each text covers the differences; PN and PS are related to birth, faith, and death; US contains adab values; PI contains the values ​​of a wife's etiquette; and RNY relates to the greatness of Allah through the stories of the Prophets and Apostles. The form of the wawacan text in the script has an important role in efforts to spread Islamic teachings in the Tatar Sunda. Keywords: manuscript, wawacan, broadcast media, Islamic teachings